Characterization of the New Immune Suppressive Anti Human CD83 Monoclonal Antibody 3C12C in Non-Human Primates. (July 2018) - Ju, Xinsheng; Bryant, Christian E; Pears, Suzanne; Sunderland, Neroli; Heffernan, Scott; Hennessy, Annemarie; Fromm, Phillip D; Lee, Kenneth; Clarke, Candice; Silveira, Pablo A; Tsonis, Con; Clark, Georgina J; et al.
Abstract : Introduction: CD83 is a member of the Ig superfamily. It is membrane bound on activated dendritic cells (DC) and B cells. We developed a potential therapeutic human anti-human CD83 monoclonal antibody (3C12C) and showed it prevents graft versus host disease in a human PBMC mouse xenograft model. After establishing that 3C12C binds to non-human primate (NHP, baboon Papio Hamadryas) cells, we tested 3C12C in vivo in NHPs before a first in man, first in class, Phase I clinical trial. Methods: Five baboons received 3C12C (1, 5, 10mg/kg, iv) or human IgG 10mg/kg on d0, 7, 14 and d21. Peripheral blood and serum were collected weekly (x4) then every 4 weeks (x2). Bone marrow and lymph node (LN) biopsies were taken at d28. Blood counts and biochemistry were monitored. Flow cytometry analysis followed the PBMC DC subsets, B cells and T cells and bone marrow haematopoietic stem cells. Immune histological studies were performed on LNs. Results: All 5 animals remained well following anti-CD83 antibody injection. 3C12C did not change blood counts or liver function. CD4+T, CD8+T and B cells remained normal to d84. 3C12C injection increased peripheral Treg transiently at d21. 3C12C reduced blood CD1c+DC in a dose dependent manner. CD1c+DC were reduced in LN. 3C12C had no influence on bone marrow hematopoietic stem cell numbers. Conclusion: Our results demonstrate that 3C12C is safe in NHPs and that it reduced activated DC numbers. This data will facilitate our planned Phase I trial of 3C12C in allogenic hematopoietic stem cell transplantation.